C-547, a 6-methyluracil derivative with long-lasting binding and rebinding on acetylcholinesterase: Pharmacokinetic and pharmacodynamic studies. (15th March 2018) - Petrov, Konstantin; Zueva, Irina; Kovyazina, Irina; Sedov, Igor; Lushchekina, Sofya; Kharlamova, Alexandra; Lenina, Oksana; Koshkin, Sergei; Shtyrlin, Yurii; Nikolsky, Evgeny; Masson, Patrick
Abstract: C-547, a potent slow-binding inhibitor of acetylcholinesterase (AChE) was intravenously administered to rat (0.05 mg/kg). Pharmacokinetic profiles were determined in blood and different organs: extensor digitorum longus muscle, heart, liver, lungs and kidneys as a function of time. Pharmacokinetics (PK) was studied using non-compartmental and compartmental analyses. A 3-compartment model describes PK in blood. Most of injected C-547 binds to albumin in the bloodstream. The steady-state volume of distribution (3800 ml/kg) is 15 times larger than the distribution volume, indicating a good tissue distribution. C-547 is slowly eliminated ( k el  =  0.17 h −1 ; T 1/2  = 4 h) from the bloodstream. Effect of C-547 on animal model of myasthenia gravis persists for more than 72 h, even though the drug is not analytically detectable in the blood. A PK/PD model was built to account for such a pharmacodynamical (PD) effect. Long-lasting effect results from micro-PD mechanisms: the slow-binding nature of inhibition, high affinity for AChE and long residence time on target at neuromuscular junction (NMJ). In addition, NMJ spatial constraints i.e. high concentration of AChE in a small volume, and slow diffusion rate of free C-547 out of NMJ, make possible effective rebinding of ligand. Thus, compared to other cholinesterase inhibitors used for palliative treatment of myasthenia gravis, C-547 is the most selective drug, displays a slow pharmacokinetics, and has the longest duration of action. This makes C-547 a promising drug leader for treatment of myasthenia gravis, and a template for development of other drugs against neurological diseases and for neuroprotection. Graphical abstract: Highlights: C-547, a 6-methyluracil derivative, is a selective slow-binding inhibitor of AChE. Administered to rat, C-547 is slowly eliminated from bloodstream. Long lasting effect on myasthenia gravis model persists >72 h. Micropharmacodynamic mechanisms allow rebinding to neuromuscular junction AChE. Interest for palliative treatment of myasthenia gravis .